The Creation of Human in Qur’an - Saifuddin, Hadid Humaid; Ibrahim, Muhammad Fikri; Permana, Yana; Yusron, Muhammad Agus (Journal of Ulumul Qur'an and Tafsir Studies, 2023)
The focus of this article is on the depiction of the creation of mankind in the Qur'an, and its subsequent interpretation. The aim of this research is to examine scientific verses related to human creation as presented in the Qur'an. This study employs a qualitative comparative method and utilizes a literature review approach, with data sourced from the book "Scientific Interpretation". Data collection involved search methods, while content analysis was used for data analysis. The article concludes that there are five stages of human development presented in the Qur'an, namely Nutfah (sperm), 'Alaqah (clot of blood), Mudhghah (lump of flesh), 'Idzam (bone), and Lahm (flesh or muscle). Its objective is to broaden our understanding of the various interpretations of the verse on human creation.